The Regulations of Sales by Model in Jordanian Law and Islamic Jurisprudence - boutosh, Ahmad; Balas, Hashim; Alsmadi, Mamoon Suliman (Journal of Ecohumanism, 2024)
The study aimed to elucidate the legal and regulatory treatment when sold goods do not conform to the model accepted by the buyer, utilizing a descriptive-analytical and comparative approach. It was divided into two sections. The first section expounded on model-based sales in Islamic jurisprudence, identifying various types in view of different models and the Islamic jurisprudential stance on such sales. The second section addressed model-based sales in Jordanian civil law under Articles 468 and 469. Key findings revealed the Jordanian legislator’s recognition of the model-based sale contract and formulation of regulations in the Civil Law. However, it did not cover all related provisions, leaving other matters subject to general rules. The study recommends the necessity for the Jordanian legislator to expand provisions for model-based sales in the Civil Law and include detailed regulations.